Study on the use, acceptability and implementation of the Unified Protocol in general health psychologists in Spain - Peris Barquero, Óscar; Ósma, Jorge Javier; Martínez-Segura, Violeta (Anales de Psicología / Annals of Psychology, 2022)
The dissemination of evidence-based psychological treatments (EBPT) is a pending task for Clinical Psychology. Through an online survey and following the Theoretical Framework of Acceptability, we analyzed the opinions about use, acceptability and intention to use in the future of the Unified Protocol for the transdiagnostic treatment of emotional disorders (UP) in a sample of 153 professionals of General Health Psychology (GHPs). All participants took a training course in the UP and were grouped depending on their previous experience in the UP application. The results showed high scores in acceptability and intention to use in the future in GHPs regardless of the group. Finally, statistically significant correlations were found between intention to use in the future and affective attitude, consistency of the intervention and perceived efficacy (in both groups) and self-efficacy (in the group of GHPs without experience in the use of UP). The UP is an EBPT that presents high levels of acceptance and intention to use by the GHPs who received training in this intervention, this will facilitate its dissemination and implementation and will allow a greater number of people to benefit from this treatment.